Madagascar : Joint Bank-Fund Debt Sustainability Analysis, 2018 Update - International Development Association; International Monetary Fund (World Bank, Washington, DC, 2018)
Madagascar’s risk of external debt distress is assessed to be moderate, in line with the last debt sustainability analysis (DSA) of June 2017, since the dynamics of Madagascar’s external public and publicly-guaranteed (PPG) debt remain sustainable under the baseline. The public DSA shows total (domestic and external) PPG debt is also sustainable under the baseline, so risks to domestic debt are not assessed as significant. However, stress tests breach the prudent benchmark for the public DSA (covering both domestic and external debt) and, in only some instances, for the external DSA. The analysis suggests that shocks to gross domestic product (GDP) growth are the main potential source of vulnerability, especially for the public DSA. A weaker currency, widened fiscal deficits, lower exports, or higher interest rates present additional risks. This DSA reflects updated and more detailed loan data, which include marginally less favorable financing conditions than in the last DSA.